The effects of the popularity of secondhand garments on boutique stores in Baguio City - Tudlong, Jennette Tarlit; Mayo, Adelaida Villaraza (1998.)
This research is about the effects of increasing purchase and personal use of secondhand garments by women from the B and C market on the overall sales of sports wear boutiques in Baguio City. It gives an overview on the rising popularity and saleability of thrift stores and secondhand clothes. This study is important because it presents a picture of the city's garment industry. This thesis is confined only to two (2) types of garment stores selling sports wear garments, namely: boutique and thrift stores. Ten (10) boutique owners and twenty (20) selected buyers and users of "segunda- manos" participated during the survey. They were chosen by means of purposive sampling. To obtain the needed data, questionnaires were utilized. Data gathered showed a change in attitude towards thrift stores and secondhand garments by the people from the B and c strata. Definitely, there was an increase of popularity and acceptance to these types of stores and garments. People buy here because of the availability of the original, famous brand and fashionable garments in very low prices. Most boutique owners admit that the overall sales of their stores are affected by the presence of thrift stores and its increasing clientele. To cope with this situation,boutique retailers started widening the type of merchandise they offer. They started selling accessories such as wallets, belts, watches, fashion jewelry, bags and shoes to help increase their sales output.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Garments; Used clothing industry -- Philippines